Representation of Social Criticism through Morgans Journalist Characters in One Piece Anime: Examining the Meanings Behind and Propaganda - Triwiyoso (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2024)
This research analyzes the representation of social criticism through the journalist character Morgans in Eiichiro Oda’s manga series One Piece. The focus of this study is on the dilemmas faced by Morgans as a journalist in balancing journalistic integrity against political and power pressures. The method used is qualitative analysis with a semiotic approach to examine the meanings behind Morgans' actions and decisions in several critical chapters. The findings reveal that Morgans serves not only as a conveyer of information but also as a tool of propaganda, reflecting the complex reality of the media world. This study highlights how Oda uses Morgans to critique the role of media in shaping public opinion and manipulating facts. Morgans represents the ethical challenges in journalism, where the truth is often compromised for specific interests.